MATERNAL PERCEPTIONS OF PARENTING FOLLOWING AN EVIDENCE‐BASED PARENTING PROGRAM: A QUALITATIVE STUDY OF LEGACY FOR CHILDRENTM. Issue 4 (28th June 2017) - Hartwig, Sophie A.; Robinson, Lara R.; Comeau, Dawn L.; Claussen, Angelika H.; Perou, Ruth
ABSTRACT: This article presents the findings of a qualitative study of maternal perceptions of parenting following participation in Legacy for Children TM ( Legacy ), an evidence‐based parenting program for low‐income mothers of young children and infants. To further examine previous findings and better understand participant experiences, we analyzed semistructured focus‐group discussions with predominantly Hispanic and Black, non‐Hispanic Legacy mothers at two sites ( n = 166) using thematic analysis and grounded theory techniques. The qualitative study presented here investigated how mothers view their parenting following participation in Legacy, allowing participants to describe their experience with the program in their own words, thus capturing an "insider" perspective. Mothers at both sites communicated knowledge and use of positive parenting practices targeted by the goals of Legacy ; some site‐specific differences emerged related to these parenting practices. These findings align with the interpretation of quantitative results from the randomized controlled trials and further demonstrate the significance of the Legacy program in promoting positive parenting for mothers living in poverty. This study emphasizes the importance of understanding real‐world context regarding program efficacy and the benefit of using qualitative research to understand participant experiences.